Thomas Piketty's capital & ideology : a graphic novel adaptation - Alet, Claire (Abrams ComicArts, 2024)
"Thomas Piketty's powerful and bestselling Capital and Ideology is now available in this accessible and richly illustrated full-color graphic novel format. Praised by Piketty himself as a 'magnificent adaptation' of his original book, this graphic novel adaptation is perfect for anyone looking to understand the wealth gap and why society is the way it is today. Claire Alet and Benjamin Adam make the original work's ideas more accessible through the addition of a family saga. Jules, the main character, is born at the end of the 19th century. He is a person of private means, a privileged figure representative of a profoundly unequal society obsessed with property. He, his family circle, and his descendants will experience the evolution of wealth and society. Eight generations of his family serve as a connecting thread running through the book, all the way up to Léa, a young woman today, who discovers the family secret at the root of their inheritance. The book concludes with six compelling proposals for participatory socialism in the 21st century"--